Do leases expand debt capacity? - Schallheim, James; Wells, Kyle; Whitby, Ryan J. (Journal of Corporate Finance, 2013)
Theoretically and empirically, debt and leases have been shown to be both substitutes and complements. To explore the relation, we divide our sample into two subsets: those that exhibit a complementary relation (43% increase debt after increasing leases), and those that exhibit a substitutionary relation (57% decrease debt after increasing leases). For complement firms, we find a significant negative relation between leasing and the firm's size, marginal tax rate, and z-score, consistent with “complementary” theories. For substitute firms, we find a positive and significant relation between leasing, the marginal tax rate and changes in cash. We also find a significant positive stock market reaction to the announcement of the SLB, which is stronger for the complement subset of firms.